Makna ‘Tafakhur’ dan ‘Takatsur’ dalam Al Qur’an dan Relevansinya dengan Gaya Hidup Hedonisme (Analisis Penafsiran Buya Hamka dan Quraish Shihab terhadap Q.S. Al Hadid Ayat 20 dalam Tafsir Al Azhar dan Al Misbah) - Yuwanti, Bening; Amir, Sulaiman Muhammad; Sari, Winda (Asian Journal of Islamic Studies and Da'wah, 2024)
With the times and technology continuing to develop, almost all areas of life are experiencing changes. Enjoying all pleasures is the goal of human life in this world. Hedonism does not only appear among students or students, but appears to be widespread in various circles of society. Most hedonistic behavior starts with rich people who always care about their appearance and enjoy life to the fullest by socializing, eating, traveling and having fun with like-minded people, which eventually spreads to various groups of society who lack living conditions. So for this discussion the author is interested in the discussion of hedonism. The focus of this research problem is describing hedonism as explained in Q.S Al-Hadid verse 20 in Tafsir Al-Azhar and Al-Misbah and focuses on the comparison (comparison: Similarities and differences) between Tafsir Al-Azhar and Al-Misbah in interpreting verse 20 of Q.S Al-Hadid. To develop deeper research, qualitative research is used with the approach used, namely the library approach or what is commonly known as library research. Collect research materials using documentary techniques, comparative analysis methods in processing materials and conclusions at the end of writing. The results of this research are the meaning of Tafkhur, Takatsur, and life. Tafakhur, Takatsur, and Hedenism in Surah Al-Hadid verse 20, the perspective of Tafsir Al-Azhar and Tafsir Al-Misbah includes being careless about the brilliance of worldly life. A comparison of the similarities between the two interpretations is in the explanation of the meaning of Tafakhur, Takatsur, and the life of hedonism. Meanwhile, in interpreting hedonism, the two commentators have differences in that Quraish Shihab's discussion of the verse about hedonism is more extensive and is also correlated with other verses. Meanwhile, Buya Hamka only focuses on understanding the nature of the world and worldly matters.